Компьютерное моделирование электротепловых процессов в полимерной изоляции кабеля с воздушным включением при возникновении единичного частичного разряда - Кучерявая, И.Н. (Технічна електродинаміка, 2011)
Coomputer modeling of electric and thermal fields in the polyethylene insulation of power cable containing air inclusion is carried out for the case of initiating of single partial discharge. The discharge is considered as transient process in heterogeneous dielectric characterized by changing conductivity. The mathematical model is realized by finite-element method in Comsol. As shown by means of numerical simulation, during single partial discharge the temperature of air inclusion with 10 μm radius momentarily increases by 2–4 °C.